Iterative reconstruction and automatic tube voltage selection reduce clinical CT radiation doses and image noise. Issue 1 (February 2018) - O'Hora, L.; Foley, S.J.
Abstract: Introduction: Computed Tomography (CT) use has increased in recent years with trends indicating increasing population doses as a result. Optimization of clinical radiation doses through technological developments has demonstrated potential to reduce patient dose from CT. This study aimed to quantify these dose reductions across a large clinical cohort. Methods: Patient cohort was divided into three groups, assigned by CT optimisation technique. Group one underwent scanning with automated tube current modulation only. Group two underwent scanning with automated tube current modulation and iterative reconstruction and group three underwent scanning with automated tube current modulation, iterative reconstruction and automatic tube voltage modulation. Patient dose length product doses were retrospectively collected for the three groups. Clinical radiation doses between the groups were compared for four common CT examinations (Brain, pulmonary angiography, abdomen and thorax abdomen pelvis scans). Results: Of 4011 patients, group one comprised of 1643 patients (40.96%), group two 1077 patients (26.85%) and group three 1291 patients (32.19%). No differences were found when comparing AP diameter between groups (p ≥ 0.05). Statistically significant dose reductions of 16–31% were achieved using iterative reconstruction alone (p = 0.001) and 24–42% with both iterative reconstruction and automatic tube voltage selection (p = 0.001). Objective noise improved when iterative reconstruction was used (p < 0.05). Conclusion: The application of optimization software confers significant dose savings during routine clinical CT examinations. Figures are based on a large clinical cohort, with equipment, staff and procedural protocols remaining consistent throughout. Dose reductions are likely to reflect the clinical dose reducing potential of the optimization software investigated. Highlights: CT data from 4011 patients (4 protocols) were retrospectively collected from PACS. Patients were split into groups depending on dose minimisation software available. Iterative reconstruction (IR) reduced the mean DLP by 16–31%. IR and automated tube voltage selection reduced the mean DLP by 24–42%. Image noise was statistically reduced when using IR.